2012
DOI: 10.1002/hed.23131
|View full text |Cite
|
Sign up to set email alerts
|

Neck and shoulder function in patients treated for oral malignancies: A 1‐year prospective cohort study

Abstract: Neck dissection, tumor site, and extensive reconstruction are related to deterioration of shoulder function shortly after intervention. Maximal active shoulder abduction was affected most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 45 publications
5
38
4
1
Order By: Relevance
“…Others have shown that disability improved with time, and rehabilitation played an important role in promoting function and reducing pain. 9,[21][22][23][24] Some studies have focused on wrist mobility, but the effect of RFF flap harvest on this parameter is unclear. [7][8][9][10] In addition, it has been shown that objective measurements do not accurately reflect the patient's experience.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that disability improved with time, and rehabilitation played an important role in promoting function and reducing pain. 9,[21][22][23][24] Some studies have focused on wrist mobility, but the effect of RFF flap harvest on this parameter is unclear. [7][8][9][10] In addition, it has been shown that objective measurements do not accurately reflect the patient's experience.…”
Section: Discussionmentioning
confidence: 99%
“…Up to one year after surgery, previous studies show patients undergoing nerve sparing surgery have limitations in shoulder flexion and abduction ranging from 140–160 degrees, while those with nerve sacrificing surgery are often limited to less than 140 degrees of flexion or abduction. 7,21,23,24,36 In our study, subjects with nerve sparing surgery have fewer limitations in ROM compared to nerve sacrifice. However, average ROM measurements are slightly lower in our cohort of 5-year survivors than previous studies of 1-year survivors.…”
Section: Discussionmentioning
confidence: 57%
“…Other studies have found reduced cervical motion, which degrades QOL and upper body function. 23 We did not include electromyography to delineate the occurrence of muscle denervation or signs of reinnervation in the trapezius. 21 Future studies should also include a measure of psychological depression to assess the effect of mood disorder on QOL.…”
Section: Discussionmentioning
confidence: 99%
“…En cas de nécessité de section du nerf spinal pour des raisons carcinologiques, la conservation des racines du plexus cervical permet de limiter les douleurs [11] (niveau de preuve 4). Lorsque le nerf spinal est conservé, la limitation de l'extension du curage permet de diminuer les douleurs postopératoires [12] (niveau de preuve 4), surtout lorsque les aires ganglionnaires situées au contact du nerf spinal (IIB et V) sont épargnées [13][14][15] (niveau de preuve 4). Le monitoring du nerf spinal pendant la chirurgie cervicale n'a pas fait la preuve d'un intérêt pour diminuer les douleurs postopératoires [16] (niveau de preuve 4).…”
Section: Douleurs Séquellaires De La Chirurgie Ganglionnaireunclassified